THE DEVELOPMENT OF SMART CITY CONCEPT IN ROMANIA - Dragos Ionut ONESCU (International Journal of Research Science and Management, 2017)
The humanity has developed over time, mainly in urban environments and around. As with the development of large towns, cities, this has led to increased consumption, increase the amount of waste and hence the pollution of the environment. In the present paper I analyzed the concept of smart city and its applying in Romania cities